PENGUJIAN EFEK DIURETIK SARI WORTEL (Daucus carota L.) PADA TIKUS PUTIH JANTAN GALUR WISTAR (Rattus norvegicus) - Sinaga, Mery A R; Bodhi, Widdhi; Yamlean, Paulina V Y (UNIVERSITAS SAM RATULANGI, 2012)
Carrot (Daucus carota L.) is a plant which used as traditional medicine and one of its benefits isas diuretic. The research was aimed to find out diuretic effect of Carrot juice and relationship ofthe increases of Carrot juice (Daucus carota L.) concentration on white male mice strain Wistar(Rattus norvegicus). Fifteen mices were divided into five group of treatment, namely negativecontrol group (CMC 1% suspension), positive control group (furosemid suspension), 15%suspension of carrot juice group, 30% suspension of carrot juice group and 60% suspension ofCarrot juice group.The test of diuretic effect were conducted by calculate volume of excretedurine during 24 hours treatment. Data were analyzed using spss ver.19. The differences betweentreatments were analyzed using one way ANOVA.The result shows that suspension of Carrotjuice treatment increase urine volume. The increases of juice concentration shows better effect.Based on result, it can be concluded that Carrot juice possess diuretic effect (p<0,05), and thereare correlation between concentrations of Carrot juice to the increasing of urinevolume.Keywords : Carrot juice, diuretic effect, Rattus norvegicus